2014
DOI: 10.1371/journal.pone.0090103
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Adapted Hypertension Education (CAHE) to Improve Blood Pressure Control and Treatment Adherence in Patients of African Origin with Uncontrolled Hypertension: Cluster-Randomized Trial

Abstract: ObjectivesTo evaluate the effect of a practice-based, culturally appropriate patient education intervention on blood pressure (BP) and treatment adherence among patients of African origin with uncontrolled hypertension.MethodsCluster randomised trial involving four Dutch primary care centres and 146 patients (intervention n = 75, control n = 71), who met the following inclusion criteria: self-identified Surinamese or Ghanaian; ≥20 years; treated for hypertension; SBP≥140 mmHg. All patients received usual hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(123 citation statements)
references
References 49 publications
2
118
0
3
Order By: Relevance
“…We observed that 89% of the patients completed all educational sessions. Studies of similar educational interventions in primary care settings in Europe and the USA recorded lower attendance rates, namely 79% and 58% [23] [41]. The high attendance rate in this study suggests that CHEP responded to patients' needs, which is plausible in the light of a previous qualitative study that was conducted in the area [29].…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…We observed that 89% of the patients completed all educational sessions. Studies of similar educational interventions in primary care settings in Europe and the USA recorded lower attendance rates, namely 79% and 58% [23] [41]. The high attendance rate in this study suggests that CHEP responded to patients' needs, which is plausible in the light of a previous qualitative study that was conducted in the area [29].…”
Section: Discussionsupporting
confidence: 45%
“…The content of CHEP was inspired by a hypertension education program that was developed by Beune et al [23], and results of a previous interview study with hypertensive patients of OOH [29]. All patients were randomly assigned to a group of 12 -15 "trainees" which held the same composition throughout the program.…”
Section: Intervention-chepmentioning
confidence: 99%
“…Telemonitoring interventions included use of SMBP and telephone counseling, 37 SMBP plus weight and exercise self-monitoring, 30 SMBP in combination with telecounseling that targeted blood pressure [BP] goals, 27 use of medication protocol adjustments that targeted BP goals and BP transmitted from SMBP by participants, 38 and SMBP plus tailored lifestyle modification (eg, DASH [Dietary Approaches to Hypertension] diet, medication use). 29 Behavioral interventions reported in 6 articles 28,34,36,[39][40][41] did not include the use of SMBP. Nurses most frequently provided the TPE to patients with hypertension, delivering TPE by telephone or in person.…”
Section: Barnason Et Al Tpe Interventions For Self-managementmentioning
confidence: 99%
“…Nurses most frequently provided the TPE to patients with hypertension, delivering TPE by telephone or in person. Behavioral research interventions included hypertension self-management-tailored education based on stage of change, 34 culturally appropriate nurse-led lifestyle interventions for African immigrants, 28 Mediterranean diet counseling and ambulatory BP monitoring, 36 and the use of self-affirmation to overcome medication adherence barriers. 39 Two studies implemented team-led and team-delivered behavioral interventions.…”
Section: Barnason Et Al Tpe Interventions For Self-managementmentioning
confidence: 99%
See 1 more Smart Citation